KEPUASAN BERDASARKAN PERSEPSI DAN HARAPAN WALI MURID TK X DI KABUPATEN LUMAJANG - Noer Aisyah Barlian (Jurnal Ilmu Manajemen Advantage, 2018)
This study aims to determine the perceptions and expectations of guardians of kindergarten X on the satisfaction of guardians of TK X students in Lumajang District. This research is expected to give description about perception and expectation of X kindergarten students and their satisfaction toward TK X in Lumajang Regency. This research prioritizes the variables of perception, expectation and satisfaction of guardian of pupil in TK X of Lumajang Regency. This research takes samples of all X TK students in Lumajang District. The research method is descriptive by using questionnaires distributed to QK X pupil in Lumajang District. The result of this research is the satisfaction of the student guardian in TK X of Lumajang Regency to the highest service quality in tangible dimension, and the expectation and the perception of the guardian of the students on the quality of service is very satisfied. Furthermore, this research is expected to contribute in the development of the study of management science, especially human resources management, so it can be a reference and development for further research.